The Phenomenon of Crisis of Religious Understanding in the Midst of the Covid-19 Pandemic - Alghiffary, Muhammad; Safitri, Eka; Sa’dudin, Ihsan; Al Khasy, Moh. Ali Qorror; Siregar, Nasrun Salim (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
Covid-19 affects the established order of worship. Muslims are required to wear masks, keep their distance, and eliminate greetings during congregations. At certain times, mosques are also required to close temporarily to prevent the spread of the virus. In fact, these rules are not obeyed by the Muslim community in the city of Pekalongan, in fact, some pilgrims oppose it. This study aims to analyze the relationship of health protocol practice with religious understanding and the role of mosques in helping victims affected by covid-19. The study uses qualitative methods in which the main data in the form of words and actions are taken using observation, interview and documentation techniques. Data in the form of words was taken using interview techniques to 27 pilgrims. The data in the form of actions was taken using observation techniques by observing religious phenomena in 12 mosques. Both data are documented using recordings and images as a form of data validation. The results of this study showed a crisis of religious understanding experienced by mosque administrators and worshippers. The management is adamant not to close the mosque in the midst of the pandemic and is reluctant to allocate infaq to the social realm of victims affected by covid-19. The pilgrims are divided into three groups: trust, doubt, and distrust of the coronavirus. However, it does not affect the effectiveness of preventive measures instructed by the government. Most pilgrims apply health protocols. Some pilgrims also consider sharia rules to be above government rules, so religious activities must still be carried out